Neuronal ablation of mt-AspRS in mice induces immune pathway activation prior to severe and progressive cortical and behavioral disruption - Nemeth, Christina L (Exp Neurol, 2019)
Leukoencephalopathy with brain stem and spinal cord involvement and lactate elevation (LBSL) is a rare, slowly progressive white matter disease caused by mutations in the mitochondrial aspartyl-tRNA synthetase (mt-AspRS, or DARS2). While patients show characteristic MRI T2 signal abnormalities throughout the cerebral white matter, brain stem, and spinal cord, the phenotypic spectrum is broad and a multitude of gene variants have been associated with the disease. Here, Dars2 deletion from CamKIIα-expressing cortical and hippocampal neurons results in slowly progressive increases in behavioral activity at 5 months, and culminating by 9 months as severe brain atrophy, behavioral dysfunction, reduced corpus callosum thickness, and microglial morphology indicative of neuroinflammation. Interestingly, RNAseq based gene expression studies performed prior to the presentation of this severe phenotype reveal the upregulation of several pathways involved in immune activation, cytokine production and signaling, and the defense response regulation. RNA transcript analysis demonstrates that activation of immune and cell stress pathways are initiated in advance of a behavioral phenotype and cerebral deficits. An understanding of these pathways and their contribution to significant neuronal loss in CamKII-Dars2 KO mice may aid in deciphering mechanisms of LBSL pathology.